Comprehensive exergo- sustainability analysis for a next generation aero engine - Aygun, Hakan; Erkara, Seref; Turan, Onder (Pergamon-Elsevier Science Ltd, 2022)
In the present study, the exergetic performance behaviours of a variable cycle engine (VCE) which is considered as an alternative engine for the fighter aircraft were analysed for eight flight phases excluding critical fighter phases. In this context, performance analysis of the variable cycle engine model was parametrically performed by on-design relations of an afterburner turbofan. These results were compared with those of conventional military turbofan (CMT) engine. Next, exergetic parameters per-taining to the VCE were measured on component-basis for eight flight phases. Moreover, five exergetic sustainability indexes of the VCE model at all flight phases were investigated in order to observe effects of flight phases on these metrics and these outcomes were compared with the conventional one. Ac-cording to comparative performance analysis, SFC value of the VCE for cruise phase was estimated as 23.89 g/kN.s whereas that of the CMT engine was computed as 27.25 g/kN.s. On the other hand, the component-based results illustrate that exergy efficiency of the combustor of the VCE has relatively low values ranging from 83.65% to 89.06%, whereas those of high pressure and low pressure turbines have relatively high ratio at concerned flight points. Furthermore, the whole engine-based results show that exergy efficiency of VCE is approximately varies between 7.45% and 31.39% whereas that of the CMT engine changes between 6.31% and 21.5% throughout flight phases. Finally, exergetic sustainability index was calculated the highest at subsonic cruise phases. Namely, it is estimated between 0.45 and 0.6 for the VCE and between 0.31 and 0.34 at these phases for the CMT engine. It is thought that studying exergetic parameters for a military aircraft during the important flight phases could help in understanding which flight segment is useful in terms of sustainability. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: Flight mission; Exergy; Energy; Sustainability; Variable cycle; Turbofan